2016
DOI: 10.4103/0973-029x.185932
|View full text |Cite
|
Sign up to set email alerts
|

Enigmatic insight into collagen

Abstract: Collagen is a unique, triple helical molecule which forms the major part of extracellular matrix. It is the most abundant protein in the human body, representing 30% of its dry weight. It is the fibrous structural protein that makes up the white fibers (collagen fibers) of skin, tendons, bones, cartilage and all other connective tissues. Collagens are not only essential for the mechanical resistance and resilience of multicellular organisms, but are also signaling molecules defining cellular shape and behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 33 publications
1
42
0
1
Order By: Relevance
“…For example, we found that IFN-inducing antivirus proteins such as Ifit2, Ifit3, Mx2, and ApoL9b were downregulated in activated GOLPH2 KO BMDCs, which indicates that GOLPH2 may play a positive role in host resistance to viral infections. Abnormal expression of collagen proteins could lead to collagen diseases, which are a heterogeneous group of systemic inflammatory diseases of autoimmune origin that affect a wide range of organs and systems, including systemic lupus erythematosus and rheumatoid arthritis (48,49). We found that col1a2, col3a1, col5a2, and col8a1 were upregulated in resting GOLPH2 KO cells, suggesting the potential involvement of GOLPH2 in the pathogenesis of these autoimmune diseases (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 77%
“…For example, we found that IFN-inducing antivirus proteins such as Ifit2, Ifit3, Mx2, and ApoL9b were downregulated in activated GOLPH2 KO BMDCs, which indicates that GOLPH2 may play a positive role in host resistance to viral infections. Abnormal expression of collagen proteins could lead to collagen diseases, which are a heterogeneous group of systemic inflammatory diseases of autoimmune origin that affect a wide range of organs and systems, including systemic lupus erythematosus and rheumatoid arthritis (48,49). We found that col1a2, col3a1, col5a2, and col8a1 were upregulated in resting GOLPH2 KO cells, suggesting the potential involvement of GOLPH2 in the pathogenesis of these autoimmune diseases (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Under polarized light, collagen types were identified through differences in birefringence. Focusing on the most abundant type of collagen, type 1 collagen (yellow birefringence), great differences were found between peri‐implantitis and periodontitis. Overall, teeth had more type 1 collagen than implants.…”
Section: Discussionmentioning
confidence: 99%
“…Collagens are, in most part, fibrous structural proteins that occur in the connective tissues (Deshmukh et al 2016). Collagens I and III are expressed in uninduced MM and their expression switches to type IV (Ekblom et al 1981), a process that is coupled with the formation of the BM and MET.…”
Section: Collagensmentioning
confidence: 99%